Aquatlantic - Carpinteri, Giorgio, 1958- (Fantagraphics Books Inc., 2020)
" In this graphic novel, Aqualantics maintain a fragile peace with their "surface brothers"- as long as their world remains a myth. But when an actor who plays the character of the "indefensible Earthman," all cynicism and vulgarity, is gradually possessed by his role, a chain reaction jeopardizes the entire kingdom and the uneasy peace between the two species. Giorgio Carpinteri's sheer graphic brilliance- fusing aspects of Futurism, Cubism, Russian Constructivism, and German Expressionism with echoes of Bauhaus and distinct whims of Art Deco- would be enough to carry this brilliant fantasy, but Aqualantic is also a lyrical, allegorical masterpiece exploring the relationship between the conscious and unconscious, the known and the unknown. Full-color illustrations throughout."--Amazon.